2017
DOI: 10.1039/c7cc02063e
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed, aminoquinoline-directed arylation of phosphonamidate and phosphinic amide sp3 C–H bonds

Abstract: Aminoquinoline-directed, palladium-catalyzed sp3 C–H bond arylation in phosphonamidates and phosphinic amides is reported. The reaction employs Pd(OAc)2 catalyst at 10 mol % loading and cesium phosphate or potassium carbonate base in 1,2-dichlorobenzene solvent. Directing group can be removed under basic conditions to afford phosphonic acid esters. The chemistry described here is the first example of unactivated sp3 C–H bond arylation by using a phosphorus-containing directing group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In 2017, the Daugulis group reported a palladium-catalyzed, 8-aminoquinoline-directed β-C­(sp 3 )–H arylation of phosphonamidates and phosphinic amides (Scheme a) . Unlike the arylation of aliphatic carboxamides, only primary C­(sp 3 )–H bonds could be functionalized in this protocol.…”
Section: Palladium-catalyzed Coordination-assisted C(sp3)–h Functiona...mentioning
confidence: 96%
See 1 more Smart Citation
“…In 2017, the Daugulis group reported a palladium-catalyzed, 8-aminoquinoline-directed β-C­(sp 3 )–H arylation of phosphonamidates and phosphinic amides (Scheme a) . Unlike the arylation of aliphatic carboxamides, only primary C­(sp 3 )–H bonds could be functionalized in this protocol.…”
Section: Palladium-catalyzed Coordination-assisted C(sp3)–h Functiona...mentioning
confidence: 96%
“…205 In 2017, the Daugulis group reported a palladium-catalyzed, 8-aminoquinoline-directed β-C(sp 3 )−H arylation of phospho- namidates and phosphinic amides (Scheme 69a). 206 Unlike the arylation of aliphatic carboxamides, only primary C(sp 3 )−H bonds could be functionalized in this protocol. Palladiumcatalyzed, 8-aminoquinoline-directed arylation of γ-C(sp 3 )−H bonds via a six-membered cyclopalladation pathway was developed by the Maiti group in 2017 (Scheme 69b).…”
Section: Palladium-catalyzed C(sp 3 )−H Functionalization Using Biden...mentioning
confidence: 99%
“… This protocol was found to be applicable for a number of unactive C­(sp 3 )–H bonds including primary and secondary C–H bonds. Following this pioneering report, many research groups reported the Pd-catalyzed C­(sp 2 )–H and C­(sp 3 )–H arylation of various aromatic or aliphatic amides with aryl iodides with the aid of an 8-AQ auxiliary. ,,, ,, …”
Section: Nn-bidentate Directing Groupsmentioning
confidence: 99%
“…Because of the synthetic importance of C(sp 3 )−H arylation, various aliphatic amides have been arylated using a Pd catalyst with the aid of an 8-AQ auxiliary; for example, the diastereoselective arylation of cyclopropanecarboxamides (Scheme 12a), 137,143 the arylation of the tertiary carbon center of cyclopropane derivatives to construct a quaternary carbon center (Scheme 12b), 144 the diarylation of cyclobutane derivatives to synthesize a complex molecule (Scheme 12c), 150 the β-methylene-C−H arylation of cycloalkyl (cyclobutane, cyclopentane, cyclohexane, and cycloheptane) carboxamides (Scheme 12d), 136 biarylation of 2°and 3°C(sp 3 )−H bonds of norbornane derivatives (Scheme 12e), 148 diastereoselective β-arylation of the secondary C(sp 3 )−H bond of aliphatic carboxamides (Scheme 12f), 134,138,154 the β-arylation of α-cyano aliphatic amides (Scheme 12g), 152 the β-arylation of α-alkoxy aliphatic amides to afford β-aryl-α-hydroxy acid derivatives (Scheme 12h), 164 the β-arylation of phosphonamidate and phosphinic amides (Scheme 12i), 174 the regioselective γ-arylation of aliphatic amides (Scheme 12j), 139 and γarylation of benzylic C(sp 3 )−H bond in furan and thiophene derivatives (Scheme 12k). 172 Notably, in all these cases, aryl iodides were used as arylating reagents.…”
Section: Nn-bidentate Directing Groupsmentioning
confidence: 99%
“…Since the pioneering works of E. J. Corey and Daugulis, 8-aminoquinoline is gradually being recognized as a general and useful bidentate directing group in transition-metal-promoted C–H bond functionalization reactions . This strategy today is not only well documented in mechanistic studies but also widely applied in the synthesis of pharmaceuticals and biological and complex natural products . However, compared to a variety of C–H bond activation reactions, using 8-aminoquinoline to achieve C–C bond and C–N bond activation-enabled transformations has been less explored.…”
mentioning
confidence: 99%